Who can better monitor a bank than another bank? Mechanisms of discipline in the Mexican interbank market - Edgar Demetrio Tovar-García (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2016)
Basel III proposes market discipline (banking disclosure requirements) as a key instrument to achieve soundness in the banking system. Consequently, it is necessary to test the presence of responses to bank risk on the part of the economic agents. This article empirically studies the mechanisms of market discipline (price, quantity, and maturity) in the interbank market: whether higher risk banks have to pay higher interest rate, and have less access to credit in the interbank market, especially for long maturity borrowing. Theoretically, bankers are well equipped to monitor other banks, but the interbank market also is a channel for contagion. Using a sample of 37 Mexican banks, from December 2008 to September 2012, and a dynamic panel model (SYS GMM estimator), I did not find evidence for discipline induced by peers.
Keywords: E59; G21; G39; 330; market discipline; interbank market; bank risk; contagion; Mexico